Ekonomisk åtstramning och flyktingmottagning (Sociologisk Forskning, 2000)
Economic tightening and refugee receptionAccording to an agreement between Malmö municipality and SIV (Swedish Immigration #Authority), 950 refugees who had been granted PUT (permanent residence permit), were allowed to move to Malmö during the 1994. Altogether, approximately 2000 foreigners were expected by local authorities to be moving to Malmö in the same period. But the real number was slightly less than 5000, and 4000 of those people were refugees. This paper aims to discuss sociologically relevant institutional aspects of this event, focusing on the consequences of the gap between the still high political aims of the Swedish welfare system and the lack of resources for these aims to be realised. The article focuses also on the related issue of citizenship. It argues that formal attributes of belonging more and more lose their importance and relevance, while at the same time substantial attributes of belonging become central as a criterion for which social groups should or not have access to material resources.